Positive correlation between PEDF expression levels and macrophage density in the human prostate1. Issue 5 (4th October 2012) - Nelius, Thomas; Samathanam, Christina; Martinez‐Marin, Dalia; Gaines, Natalie; Stevens, Jessica; Hickson, Johnny; de Riese, Werner; Filleur, Stéphanie
Abstract BACKGROUND In this study, we investigated the capacity of pigment epithelium‐derived factor (PEDF) to modulate the recruitment and the differentiation of monocytes/macrophages both in vitro and in human prostate. METHODS Using Boyden chambers, we assessed PEDF effect on the migration of monocytes and chemically activated RAW 264.7 macrophages. Normal, prostatitis, and prostate cancer specimens were retrospectively selected and examined by immunohistochemistry for PEDF expression and infiltration of immune CD68 + macrophagic cells. PEDF expression and macrophage density were then correlated with each other and clinicopathological parameters. M1 and M2 differentiation markers were quantified by qRT‐PCR, Western blotting, and ELISA. RESULTS In chemotaxis, PEDF induced the migration of monocytes/macrophages. In immunohistochemistry, macrophages were markedly increased in prostatitis and malignant compared to normal tissues. PEDF was expressed at variable levels in the stroma and epithelium. PEDF mRNA was down‐regulated in both prostate cancer and prostatitis compared to normal tissues. In correlation studies, macrophage density and PEDF expression were respectively positively and negatively associated with prostate size. Most importantly, PEDF expression positively correlated with macrophage density. Finally, PEDF stimulated the expression of iNOS, IL12, and TNFα; and inhibited IL10 and arginase 1 in mouse and human macrophages confirming a M1‐type differentiation. CONCLUSIONS Our data demonstrate that PEDF acts directly on monocytes/macrophages by inducing their migration and differentiation into M1‐type cells. These findings suggest a possible role of macrophages in PEDF anti‐tumor properties and may support further development of PEDF‐based anti‐cancer therapy. Prostate 73: 549–561, 2013. © 2012 Wiley Periodicals, Inc.